In-vitro evaluation of some generic products of atenolol commonly sold in the Saudi market - Alnuhait, Mohammed A.; Al Shammari, Abdullah S.; Mustafa E. Ahmed; Aiman A. Obaidat (Journal of Innovations in Pharmaceutical and Biological Sciences, 2016)
The specific aim of this study was to evaluate the quality of 6 atenolol generic tablet products available in the Saudi market and to compare them to the originator innovative product that is also available in the Saudi market which is TENORMIN®. This approach will be used to establish a pharmaceutical and chemical equivalence between the generic products and the originator, which can serve as an indicator of pharmacokinetic and therapeutic bioequivalence. Six different generic brands of atenolol were purchased from the retail pharmacy outlets in the city of Riyadh, Saudi Arabia. These brands were investigated according to the in-vitro compendial requirements, which include weight variation, content uniformity, tablet thickness, tablet hardness, friability and tablet disintegration and dissolution tests. These tests were performed according to the procedures and methods described by the British Pharmacopoeia (BP). All the investigated 6 generic brands of atenolol passed the standards of the BP regarding hardness, friability, weight variability, and content uniformity. In comparison to the originator product (Tenormin®), all the generic brands passed the pharmacopoeial standards for the disintegration and dissolution tests. There were no significant differences in the percent released of the active ingredient among the different brands as indicated by the results of the dissolution test. All the investigated generic products released more than 80% of the drug within 30 minutes. Based on the obtained results and in comparison with the originator product, all the tested brands are assumed to be chemically and pharmaceutically equivalent. All these products can be used as generic substitutes for the originator product.atenolol